Pastor's earthly passion honored: $1.2 million prize goes to CSU prof - Cornelius, Coleman, author; The Denver Post, publisher (Colorado State University. Libraries, 2003)
"Minister's passion takes prize."
Keywords: Rolston, Holmes, 1932-2025